The relationship between violent cartoon films and acquiring violent values and behaviors by Algerian children:: A case study of a sample of children in the wilaya of Jijel - Bougherza, Ridha; Hadid, Youcef; Menighad, Ahmed (Journal of Human Sciences, 2021)
Our study aims to demonstrate the relationship between violent cartoon films and acquiring violent values and behaviors by Algerian children. To this end and to achieve the objectives of this study, we opted for the descriptive approach associated with the use of a guided interview questionnaire applied to a research sample composed of 113 children, aged between 8 and 12 years. After choosing the appropriate statistical tools to test the hypotheses and process them as required by the study objectives, the two researchers concluded that there is a relationship between the exposure to violent cartoon films and acquiring violent values and behaviors by children.